The Relationship Between Social Comparison, Problematic Internet Use and Social Anxiety in Adolescents - Palupi, Varina Citra; Suroso; Pratitis, Niken Titi (Kirana Publisher (KNPub), 2025)
This study aims to determine the relationship between social comparison, problematic internet use and social anxiety in adolescents. Adolescence is a transitional period from childhood to adulthood, so that it makes a difference or change in the demands of the characteristics of development and growth. The research method used was quantitative correlation with a sample of 217 high school adolescents in Asemrowo District, Surabaya. Data collection instruments used three scales, namely the social anxiety scale, social comparison scale, and problematic internet use scale measured using a Likert scale. The results of the analysis show that social comparison and problematic internet use have a simultaneous relationship with social anxiety in adolescents. Teenagers with social comparison will compare themselves with others, supported by problematic internet use carried out in each teenager, so that social anxiety will increase. The next result shows that social comparison has a positive relationship with social anxiety in adolescents. This means that adolescents who compare themselves with others can increase anxiety and fear when in a social environment. The results of the third hypothesis show that problematic internet use has a positive relationship with social anxiety in adolescents. This means that teenagers who use the internet not according to their needs can increase their anxiety and fear.